The impact of product knowledge, working environment and organization commitment towards employee performance among staff at RHB Bank Berhad Kota Kinabalu / Ahmad Zaidi Tokeh and Norzaidah Madguil - Tokeh, Ahmad Zaidi; Madguil, Norzaidah (2016)
This study entitled "The Impact of Product Knowledge, Working Environment and Organization Commitment towards Employee Performance among staff at RHB Bank Berhad Kota Kinabalu" was carried out with the objectives to: (i) to evaluate the understanding of product knowledge and its impact to employee performance; (ii) to understand the effect of working environment and employee performance; and (iii) to examine organization commitment and its impact on employee performance. This study usage based on demographic characteristics (gender, age, race and department) The research is descriptive and quantitative in nature using survey method with 150 respondents selected through convenience sampling in major RHB banks in Kota Kinabalu, Sabah. The result showed that between three independent variables namely product knowledge, working environment and organization commitment have positive relationships with dependent variable, employee performance.